The Repercussions of COVID-19 Pandemic, its Socio-economic Changes, in the Jordanian Family and Ways to Prevent them (A Sociological Study) - AL-Bakar, Asem (Dirasat: Human and Social Sciences, 2022)
The repercussions of COVID-19 pandemic, its Socio-economic changes, in the Jordanian family and ways to prevent them A sociological study Abstract The current study aimed to identify the Socio-economic changes caused by the COVID-19 pandemic in the Jordanian family from the point of view of university students and the role of the Jordanian family in preventing it. Social sample surveying approach and stratified random sampling were applied. The sample consisted of (215) male and female students. Descriptive approach (percentages, advanced statistical methods were used. The results revealed that there were significant changes caused by COVID-19 on Jordanian family, including social changes represented by lack of participation in social events motivated by mitigating the negative aspects of COVID-19 and the rise in social responsibility. The results showed a change in the rituals of mourning and marriage customs; also, an increase in media follow-up by family members. The results revealed educational burden on family regarding e-learning, and indicated that the COVID-19 affected, to a moderate degree, families in terms of social stigmatization. Regarding the economic changes, there were high level economic changes affecting the Jordanian family, such as the emergence of woman’s role in the family due to her increased production responsibilities, and new productive roles like producing bread and household products to reduce family members’ leaving house to preserve their health and reduce expenses. There were additional financial burdens shouldered by family which was satisfied with providing basic materials only.